Improved particle filtering based algorithm for time delay and symbols joint estimation of PSK signals - Nan XIA; Tian-shuang QIU (Tongxin xuebao)
An adaptive particle filtering algorithm based on resampling was proposed for time delay estimation of PSK signals,which could eliminate the influence of inaccurate posterior possibility distribution caused by the small noise variance and the influence of the increase of estimation error caused by the large noise variance.Taking into account the small time delay estimation being invalid in the existing algorithms,a symbol forward and backward detection technique was applied to achieve random time delay accurate estimation in a symbol period.Otherwise,the carrier frequency offset of the received signal was estimated and compensated.Simulation results verify the novel algorithm can achieve more accurate time delay estimation and lower symbol error rate than the existing algorithm.